A highly selective and instantaneously responsive Schiff base fluorescent sensor for the "turn-off" detection of iron(iii), iron(ii), and copper(ii) ions. Issue 5 (11th January 2019) - Zhu, Xiaoyu; Duan, Yuai; Li, Po; Fan, Haiming; Han, Tianyu; Huang, Xiaonan
Abstract : A new and tri-responsive fluorescent Schiff base probe (DBAB) has been designed and developed for the recognition of iron(iii ) ions (Fe 3+ ), iron(ii ) ions (Fe 2+ ) and copper(ii ) ions (Cu 2+ ) simultaneously. Abstract : A new and tri-responsive fluorescent Schiff base probe (DBAB) has been designed and developed for the recognition of iron(iii ) ions (Fe 3+ ), iron(ii ) ions (Fe 2+ ) and copper(ii ) ions (Cu 2+ ) simultaneously. This sensor displays a favorable selectivity for Fe 3+, Fe 2+ and Cu 2+ ions over a range of other common metal cations in DMF solution, leading to prominent fluorescence on–off. The detection limits were 2.17 × 10 −6 M for Fe 3+, 2.06 × 10 −6 M for Fe 2+ and 2.48 × 10 −6 M for Cu 2+ respectively. This tri-responsive fluorescent probe for Fe 3+, Fe 2+ and Cu 2+ was distinguished by further reduction of the ascorbic acid. The recognition mechanism of DBAB toward Fe 3+, Fe 2+ and Cu 2+ has been investigated in detail by Job plot measurements and 1 H NMR.